1986
DOI: 10.1128/aac.30.4.584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clavulanic acid on the activity of ticarcillin against Pseudomonas aeruginosa

Abstract: We studied the ability of clavulanic acid (CA) to induce beta-lactamase in Pseudomonas aeruginosa isolates and what effect this might have on the susceptibilities to beta-lactam agents. We first used a disk approximation method to test 4 laboratory and 16 clinical P. aeruginosa isolates against antipseudomonal beta-lactam agents for truncation by CA and found this to be very common. All antimicrobial compounds except imipenem demonstrated truncation in the vicinity of CA. We also evaluated the extent to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In the current study, the in vitro inducer activity of clavulanate and sulbactam for organisms possessing class I enzymes was demonstrated, confirming results of previous studies (4,11,12,16,(18)(19)(20). This induction was strain and concentration dependent and occurred to a greater extent with clavulanate.…”
Section: Methodssupporting
confidence: 78%
See 4 more Smart Citations
“…In the current study, the in vitro inducer activity of clavulanate and sulbactam for organisms possessing class I enzymes was demonstrated, confirming results of previous studies (4,11,12,16,(18)(19)(20). This induction was strain and concentration dependent and occurred to a greater extent with clavulanate.…”
Section: Methodssupporting
confidence: 78%
“…shown that clavulanate and sulbactam can cause the induction of class I 13-lactamase (4,11,12,16,(18)(19)(20). In vitro antagonism has been demonstrated for most combinations of broad-spectrum ,B-lactams (including ticarcillin and cefoperazone) and clavulanate for organisms possessing class I enzymes (4,10,19).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations